Adapting prenatal iron supplementation to maternal needs results in optimal child neurodevelopment: a follow-up of the ECLIPSES Study - Lucía Iglesias-Vázquez; Carmen Hernández-Martínez; Núria Voltas; Josefa Canals; Pilar Coronel; Mercedes Gimeno; Victoria Arija (BMC Pregnancy and Childbirth, 2022)
Abstract Background Prenatal prescription of standard iron supplements to prevent iron deficiency appears not to be appropriate for all women and their children, as some women may be at risk of iron deficiency and others at risk of iron excess early in pregnancy. The present study aimed to assess whether prenatal iron supplementation adapted to the needs of each pregnant woman affects their child’s neurodevelopment. Methods Follow-up of a community-based RCT involving 503 mother–child pairs. Non-anaemic pregnant women recruited in Tarragona (Spain) early in pregnancy were prescribed a daily iron dose based on their initial haemoglobin levels: Stratum 1 (Hb = 110–130 g/L, 80 or 40 mg/d of iron) and Stratum 2 (Hb > 130 g/L, 40 or 20 mg/d of iron). Women receiving 40 mg/d were considered the control group in each Strata. The child’s neurodevelopment was assessed at 40 days of age using the Bayley Scales of Infant Development-III (BSID-III). Adjusted multiple regression models were used. Results Multiple regression analyses showed no association between the intervention and control group within each Strata on the BSID-III scores on any of the developmental scales in children, including cognitive, language, and motor development: Stratum 1 (β 1.46, 95%CI -2.15, 5.07; β 1.30, 95%CI -1.99, 4.59; and β 2.04, 95%CI -3.88, 7.96, respectively) and Stratum 2 (β -4.04, 95%CI -7.27, 0.80; β -0.36, 95%CI -3.47, 2.75; and β -3.76, 95%CI -9.30, 1.78, respectively). Conclusions In non-anaemic women in early pregnancy, no differences were found in the cognitive, language and motor development of children at 40 days of age between the dose of iron tested in each case –adjusted to initial Hb levels– compared to the dose of the control group. Further studies are guaranteed to confirm our findings. Trial registration The ECLIPSES study was registered at www.clinicaltrialsregister.eu as EudraCT number 2012–005,480-28.